2018
DOI: 10.1371/journal.pone.0206519
|View full text |Cite
|
Sign up to set email alerts
|

Leptin gene variants and colorectal cancer risk: Sex-specific associations

Abstract: BackgroundHigh levels of serum leptin and low levels of serum adiponectin are strongly correlated with obesity, a well-established risk factor for colorectal cancer (CRC). Growing evidence suggests that dysregulation of leptin and adiponectin levels may play an etiological role in colorectal carcinogenesis. We evaluated 20 candidate variants in 4 genes previously shown to alter serum leptin and adiponectin levels for associations with obesity (BMI>30 kg/m2) and CRC risk.MethodsWe analyzed 6,246 CRC cases and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 64 publications
1
23
1
Order By: Relevance
“…These data corroborate a report by Saetang et al [51], who found that low serum ADP concentration was significantly associated with the development of colorectal adenoma and early-stage colorectal carcinoma; however, in the invasive CRC group in that study, blood ADP concentration was similar to that observed in the control group. An increase in blood ADP concentration with CRC staging may suggest the appropriate response of anti-neoplasmatic ADPrelated organism activities [2,12,16,21,30,[34][35][36][37][38][39][40][41][42], which, unfortunately, were ineffective in the control of cancer growth. This suggestion is supported by the obser-vation that patients with stage II CRC had a higher ratio of ADP to TNF-alpha compared to stages I and III patients, as this accords with the existing data [30] and may be interpreted as patients with localized CRC (stages II, III, and II + III) still having a better balance between anti-(ADP) and pro-(TNF-alpha) cancerogenic adipocytokines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These data corroborate a report by Saetang et al [51], who found that low serum ADP concentration was significantly associated with the development of colorectal adenoma and early-stage colorectal carcinoma; however, in the invasive CRC group in that study, blood ADP concentration was similar to that observed in the control group. An increase in blood ADP concentration with CRC staging may suggest the appropriate response of anti-neoplasmatic ADPrelated organism activities [2,12,16,21,30,[34][35][36][37][38][39][40][41][42], which, unfortunately, were ineffective in the control of cancer growth. This suggestion is supported by the obser-vation that patients with stage II CRC had a higher ratio of ADP to TNF-alpha compared to stages I and III patients, as this accords with the existing data [30] and may be interpreted as patients with localized CRC (stages II, III, and II + III) still having a better balance between anti-(ADP) and pro-(TNF-alpha) cancerogenic adipocytokines.…”
Section: Discussionmentioning
confidence: 99%
“…LEP, along with ghrelin, mainly plays a role in the regulation of appetite and energy expenditure through decreasing orexigenic and increasing anorexigenic neuropeptide release from the hypothalamus and is recognized as a serum biomarker of total body fat mass (FM) [20]. However, in vitro, LEP also promotes colonic cell growth, proliferation, survival (antiapoptosis), immune response, migration, and angiogenesis [2,[20][21][22][23][24][25][26][27][28][29][30][31]. In a recent meta-analysis by Yang et al [17], the role of LEP as an independent factor in carcinogenesis was confirmed through associations found between LEP rs2167270 and LEP rs4731426 single-nucleotide polymorphisms, and the risk of CRC remained significant in women after adjusting for obesity [30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased blood leptin is associated with increased risk of developing breast [117] or thyroid [118] cancer. Interestingly, certain polymorphisms in the leptin gene have been associated with increased CRC in women [119]. However, no changes in serum leptin were found in CRC patients [120], and in fact, increased expression of leptin and leptin receptor in CRC samples was associated with better prognosis [121].…”
Section: Fundamental Metabolic and Systemic Adaptations Induced By Enmentioning
confidence: 99%